Quantitation of pathogenic potential of Staphylococcus aureus. - Zierdt, C H (1982)
Numerical estimates of the pathogenicity of Staphylococcus aureus strains were made for phage-typed strains from a relative incidence of significant to nonsignificant isolates from hospital patients. For a specific phage-patterned strain, the number of isolates from significant (wounds, abscesses, blood, etc.) sites was divided by the number of isolates from nonsignificant (respiratory tract, body surfaces, etc.) sites. This value, multiplied by 100, was the index of infection potential (IIP). IIP values for the S. aureus strains studied ranged from a low of 8 to a high of 50. The average IIP for all phage-patterned strains that occurred 50 or more times was 20. There was an inverse relationship between length of the phage pattern (number of the 26 typing phages that lysed the strain) and pathogenicity. Those strains with shorter phage patterns had higher IIP values and were more pathogenic. Strains lysed by one phage had an average IIP of 27, whereas those lysed by 18 phages had an average IIP of 14.